Visual, Auditory, and Tactile Learning Style in SMP Advent Unklab - Rachman, Lisa Mathilda; Sanger, Alan Hubert Frederick; Baureh, Gabriella Alleid Dian (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims and focuses on finding out the most dominant leaning styles (visual, auditory and tactile learning styles) at Unklab Adventist Middle School (SMP). This research involved 33 respondents from class VIII B SMP Advent Unklab. The total respondent sampling method was used in this research using a questionnaire as the instrument distributed to the respondents. The questionnaire used in this research, which was adapted from the University of Texas Learning Center (2006), was to find out what learning styles was the most dominant learning styles at SMP Advent Unklab. The results showed that the most dominant learning style is visual learning style (M= 3.57) although it is only slightly different from tactile (M= 3.53), and the last one was auditory (M= 3.47).